2013
DOI: 10.1021/jp403796h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control and Catalytic Reactivity of Peptide-Templated Pd and Pt Nanomaterials for Olefin Hydrogenation

Abstract: Diverse classes of metallic nanostructures have been explored recently for a variety of applications, including energy efficient catalytic transformations. The morphology, size, and local chemical environment of the catalytic nanomaterials can have dramatic effects on their reactivity. Herein, we demonstrate a peptide-template-based approach for the synthesis of Pd and Pt nanostructures of varying morphologies under ambient conditions. In this report, we examine the effect of the metal/peptide ratio over an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(109 citation statements)
references
References 68 publications
9
100
0
Order By: Relevance
“…The adsorption of alkene group instead of −OH group is also known to be a favorable mode of adsorption for allylic alcohols on Pd surface. 3941 …”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of alkene group instead of −OH group is also known to be a favorable mode of adsorption for allylic alcohols on Pd surface. 3941 …”
Section: Resultsmentioning
confidence: 99%
“…78,79 They found that by varying Pd/peptide ratios from 60 to 120, the shapes of Pd catalysts changed from spherical (Pd/peptide ratios = 60–80), linear/ribbon-like (90–110) to NPN (110–120) structure, but the size of these different Pd nanostructures was still constrictively controlled. 38,78 Owing to the unique ability to load selective amounts of Pd materials into the scaffolds, both the metallic surface area and the penetration depth of reagents to the Pd surface can be flexibly altered. Therefore, these R5-templated Pd catalysts were proven to be highly active in the Stille coupling reaction, the 4-nitrophenol reduction reaction, and the hydrogenation of allyl alcohol, just like the Pd4-templated Pd catalysts.…”
Section: Applications Of the Peptide-templated Noble Metal Catalystsmentioning
confidence: 99%
“…Therefore, these R5-templated Pd catalysts were proven to be highly active in the Stille coupling reaction, the 4-nitrophenol reduction reaction, and the hydrogenation of allyl alcohol, just like the Pd4-templated Pd catalysts. 38,78 On the other hand, the surface areas and the penetration depth for oxidative addition differ for Pd NPs of different shapes, thus leading to changes in their catalytic properties. 38 For spherical Pd catalyst, there exist the highest Pd surface and the largest penetration depth as a result of the high dispersity of Pd NPs.…”
Section: Applications Of the Peptide-templated Noble Metal Catalystsmentioning
confidence: 99%
“…[17][18][19][20] The selectivity in the reduction of the C=C group in the presence of other functional substituents (e.g., C=O or OH), can be controlled by a variety of parameters, such as the nature of the metal catalyst, the presence of a second metal (bimetallic catalysts), the size of metal particles and the nature of the supporting materials (electron-donating or -withdrawing ligand effects, metal-support interactions and solvent effect). [29][30][31][32][33][34][35] However, the preparation of metal NPs often involves the use of environmental unfriendly organic solvents. 27,28 In particular, some Palladium and Platinum NPs are reported to be active catalysts in the hydrogenation of unsaturated hydrocarbons or allyl alcohols.…”
Section: Introductionmentioning
confidence: 99%